If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + -10) + -1(5y + 7) = 0 Reorder the terms: (-10 + 2y) + -1(5y + 7) = 0 Remove parenthesis around (-10 + 2y) -10 + 2y + -1(5y + 7) = 0 Reorder the terms: -10 + 2y + -1(7 + 5y) = 0 -10 + 2y + (7 * -1 + 5y * -1) = 0 -10 + 2y + (-7 + -5y) = 0 Reorder the terms: -10 + -7 + 2y + -5y = 0 Combine like terms: -10 + -7 = -17 -17 + 2y + -5y = 0 Combine like terms: 2y + -5y = -3y -17 + -3y = 0 Solving -17 + -3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + -3y = 0 + 17 Combine like terms: -17 + 17 = 0 0 + -3y = 0 + 17 -3y = 0 + 17 Combine like terms: 0 + 17 = 17 -3y = 17 Divide each side by '-3'. y = -5.666666667 Simplifying y = -5.666666667
| x^2+88=7 | | 3(x-9)=6x-24 | | -9x^2+6x-1=0 | | -3(2x-4)+9x-4= | | 3(1-x)-(3+x)=2 | | -9x^2+6x-1=x | | 6x+8x+28=70 | | 6x-23=5x-23 | | 6-1x0+2/2 | | 3(x+6)=3-4(4x+3) | | 4(5+-0.25y)+y=20 | | 38x-7=26x+5 | | 0.03(7t-5)=0.21(t-4)+0.69 | | Y=5+-0.25y+5 | | -6(5-x)+2=3(x-2) | | (7/17x)+4=(1/17x)-12 | | -1.2x-0.8=1.6x+3 | | 14/4y+2/2=3y-5 | | 7x-3=7(x+2) | | -(x+7)=2(4x-4) | | 0.24-0.03(x+1)=-0.03(3-x) | | -7y-12=2y+15 | | x^3-2x-56=0 | | -5+5x=x-9 | | -6(x-2)-20=-8 | | -15=-k | | X^3+7x^2=x^2-9x | | 184/6=x/1288 | | 6x^3+20x^2=-6x | | 7m=8+5 | | -26=-7v+4(v-2) | | 4x-6=-7x+60 |